2015
DOI: 10.3390/w7062753
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Alterations of the Mures River, Romania under Ensembles of Future Climate Projections and Sequential Threats to Aquatic Ecosystem by the End of the Century

Abstract: This study aims to assess the potential alterations in the hydrological regime attributed to projected climate change in one of the largest rivers in the Carpathian Area, the Mures River, and to estimate associated threats to riverine ecosystem. The eco-hydrological model, Soil and Water Integrated Model (SWIM), was applied on the Mures River basin, calibrated and validated against records at a gauging station in Alba-Julia town. A set of nine future projections for climatic parameters under one emissions scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Similar to our results, they found a model agreement for a projected increase in winter discharge, a decrease in summer and late spring flows, as well as a prolongation of low flow periods until the end of the 21st century. While our results indicate a decrease in high flow magnitudes in this area, Lobanova et al [22] found a slight increase in median values for the duration of high flow events, but no model agreement for the number of high flow events per year.…”
Section: Comparison Of the Results To Other Available Studiescontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, they found a model agreement for a projected increase in winter discharge, a decrease in summer and late spring flows, as well as a prolongation of low flow periods until the end of the 21st century. While our results indicate a decrease in high flow magnitudes in this area, Lobanova et al [22] found a slight increase in median values for the duration of high flow events, but no model agreement for the number of high flow events per year.…”
Section: Comparison Of the Results To Other Available Studiescontrasting
confidence: 99%
“…Lobanova et al [22] carried out a small scale modeling study for a Carpathian headwater of the Mures River, analyzing different "Indicators of Hydrological Alteration" by [17] under an ensemble of various climate models (A1B). Similar to our results, they found a model agreement for a projected increase in winter discharge, a decrease in summer and late spring flows, as well as a prolongation of low flow periods until the end of the 21st century.…”
Section: Comparison Of the Results To Other Available Studiesmentioning
confidence: 99%
“…For the Middle Danube basin, the few available project studies agree on an increase in runoff in winter and, apart from less future precipitation in the summer months, make some contradictory statements regarding the rest of the year [15,54]. Though our ensemble results for the middle Danube River Basin show a larger range in the direction of change outside of the winter months, the majority of the scenarios indicate a decrease in runoff from April-September.…”
Section: Changes In Streamflow Seasonality Under Climate Changementioning
confidence: 80%
“…In recent years, the SWIM model has been applied for many river basins in Europe, Africa, Asia, and South America [32][33][34][35][36]. The modelling was focused not only on hydrological issues, but also on sediments, extreme events, crop yield, and water quality [37].…”
Section: Swim Model Descriptionmentioning
confidence: 99%